Effect of Moringa oleifera Bark Extracts on Dexamethasone-induced Insulin Resistance in Rats - Sholapur, H. N.; Patil, B. M. (Drug Research, 2013)
Experimental study has revealed the antidiabetic potentials of ethanolic extract of the bark of Moringa oleifera Lam., (Moringaceae), a multipurpose tree of south Asia.To investigate the effects of alcoholic and petroleum ether extracts of Moringa oleifera bark on acute and chronic insulin resistance induced by dexamethasone in rats.Dexamethasone (dexa) was administered for 11 days (1 mg/kg, s. c., once daily) and single dose (1 mg/kg, i. p.) to induce chronic and acute insulin resistance respectively. 2 doses each of alcoholic (AE125 and AE250 mg/kg) and petroleum ether extracts (PEE30 and PEE60 mg/kg) and single dose each of alcoholic (AE250 mg/kg) and petroleum ether extract (PEE 60 mg/kg) of Moringa oleifera bark were tested in chronic and acute studies. At the end of the studies fasting plasma glucose, triglyceride levels and oral glucose tolerance were measured.In chronic study, treatment of rats with AE125 and AE250 prevented dexamethasone-induced hypertriglyceridemia and oral glucose intolerance but not fasting hyperglycemia, whereas both PEE30 and PEE60 had no effects on any of these parameters measured except that significant reduction of triglyceride level was observed in PEE60 treated rats. Oral glucose intolerance induced by single dose administration of dexamethasone was prevented by AE250 but not by PEE60. In normal rats AE250 treatment improved the glucose tolerance, where as PEE60 had no effect on this parameter.The present study indicates that AE of Moringa oleifera prevents dexamethasone-induced insulin resistance in peripheral tissues.
Keywords: moringa oleifera; insulin resistance; dexamethasone; serum triglyceride; oral glucose tolerance test